THE Implementation Of Early Children Mathematics Educational Game Tools Tkit Mu'adz Bin Jabal: Hanifah Nur Fatha - Hanifah Nur Fatha (Universitas muhammadiyah Banjarmasin, 2022)
This observation ambitions to explain the coaching and gaining knowledge of activities of early childhood mathematics in TKIT Mu'adz Bin Jabal Cilegon. specially concerning the early early life arithmetic curriculum that takes region inside the kindergarten. The researcher additionally examines how the device of introducing mathematical concepts is implemented via the faculty to its students. looking for troubles in the area and offer solutions from the researcher's factor of view. The studies used the method of literature overview, interviews, and direct observation in processing the records. through a theoretical look at technique and character interviews, the researchers tried to definitely describe the problems that occur within the field associated with the introduction of the idea of early formative years mathematics.